Whole exome sequencing reveals inherited and de novo variants in autism spectrum disorder: a trio study from Saudi families - Al-Mubarak, Bashayer; Abouelhoda, Mohamed; Omar, Aisha; AlDhalaan, Hesham; Aldosari, Mohammed; Nester, Michael; Alshamrani, Hussain. A.; El-Kalioby, Mohamed; Goljan, Ewa; Albar, Renad; Subhani, Shazia; Tahir, Asma; et al. (Scientific reports, 2017)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with genetic and clinical heterogeneity. The interplay of de novo and inherited rare variants has been suspected in the development of ASD. Here, we applied whole exome sequencing (WES) on 19 trios from singleton Saudi families with ASD. We developed an analysis pipeline that allows capturing both de novo and inherited rare variants predicted to be deleterious. A total of 47 unique rare variants were detected in 17 trios including 38 which are newly discovered. The majority were either autosomal recessive or X-linked. Our pipeline uncovered variants in 15 ASD-candidate genes, including 5 ( GLT8D1 , HTATSF1 , OR6C65 , ITIH6 and DDX26B ) that have not been reported in any human condition. The remaining variants occurred in genes formerly associated with ASD or other neurological disorders. Examples include SUMF1 , KDM5B and MXRA5 (Known-ASD genes), PRODH2 and KCTD21 (implicated in schizophrenia), as well as USP9X and SMS (implicated in intellectual disability). Consistent with expectation and previous studies, most of the genes implicated herein are enriched for biological processes pertaining to neuronal function. Our findings underscore the private and heterogeneous nature of the genetic architecture of ASD even in a population with high consanguinity rates.